PENGARUH GREEN PRODUCTPADA MINYAK GORENG ECOPLANET TERHADAP MINAT BELI KONSUMEN - ALFA ROBY, MAHBUB (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The aims of this research are to analyze and discuss the effect of green product in ECOplanet cooking oil on customers purchase intention. The type of this research is quantitative. The sampling technique that used was purposive sampling with sample size of 110 respondents. Data analysis techniques that used are validity test, reliability test and simple linear regression analysis using PASW Statistics 18 software. Result of the research shows that there are linear relationship between independent variable and dependent variable, it means that green product on ECOplanet cooking oil has positive effect on customers purchase intention on customers of Kalimas Carrefour Surabaya that is proven by positive sign at the regression formula. Keywords: green marketing, green product, customers purchase intention.